An efficient synthesis of 3‐triazolyl‐2(1H)‐quinolones by CuTC‐catalyzed azide–alkyne cycloaddition reaction. (27th February 2013) - Messaoudi, Samir; Gabillet, Marie; Brion, Jean‐Daniel; Alami, Mouâd
Abstract : A facile and efficient Cu(I)‐catalyzed azide–alkyne cycloaddition reaction for the synthesis of a series of 3‐triazolyl‐2(1 H )‐quinolones3 have been developed using 3‐azido‐quinolin‐2(1 H )‐one as the coupling partner. The optimized reaction conditions involve the use of eco‐ friendly ethanol as the solvent in the presence of copper(I) thiophene‐2‐carboxylate as the catalyst, to afford good to excellent yields of 3‐triazolyl‐2(1 H )‐quinolone derivatives of biological interest. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The use of 3‐azidoquinolinone as partner in the copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) with terminal alkynes allows the preparation of various 3‐triazolyl‐2(1 H )‐quinolones in good yields. CuTC proved to be the best catalyst; in all cases, the reaction takes place rapidly in EtOH in the absence of any additive, and it does not require any purification step to isolate pure triazoles.